Enabling Entanglements to Emerge: Discovering Performance Curation in the Philippines. Issue 1 (1st March 2022) - Bautista, Regina
Abstract : From October 5 to 10, 2020, Performance Curators Initiative (PCI), a network of artists, curators, performance-makers, cultural workers, educators, practitioners, and enthusiasts based in the Philippines, held their third conference online via Zoom and streamed it on YouTube. Entitled "Conversations on Curation and Performance in the Time of Halting and Transformation, " I participated in this conference that opened a digital space for curators and performers around the world to talk about the effects of the global pandemic on the live arts. Connections, conversations, creative research, collaborations—as PCI founder and conference organizer Roselle Pineda notes—are the main focus of the network, which seeks to look at the relationship between "[p]erformance and curation, the role of curation in performance and role of performativity in curatorial practice" (from the network's website). Pineda had invited me to register for the conference, which was focused on the role of curator as one who activates enabling spaces.